1999
DOI: 10.1007/s002210050661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive cortical stimulation on the silent period evoked by magnetic stimulation

Abstract: The effects of repetitive transcranial stimulation (rTMS) on brain activity remain unknown. In healthy subjects, we studied the effects of rTMS on the duration of the cortical silent period (SP). Repetitive stimuli were delivered with a Cadwell High Speed Magnetic Stimulator and a figure-of-eight coil placed over the hand motor area. rTMS was delivered in trains of 11 or 20 stimuli at frequencies of 3 and 5 Hz and at stimulation intensities of 110 and 120% of motor threshold. The SP was recorded from the forea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 24 publications
3
28
0
1
Order By: Relevance
“…In an earlier study, we observed that in normal subjects rTMS delivered at frequencies of 3 and 5 Hz prolongs the duration of the SP and probably does so by altering the activity of the cortical inhibitory interneurons. 10,11 Here we now show that rTMS prolongs the cortical SP to a similar extent, also in patients with PD. The normal pattern of cortical SPs during rTMS in PD suggests that the cortical inhibitory interneurons mediating the SP as tested by rTMS function normally.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In an earlier study, we observed that in normal subjects rTMS delivered at frequencies of 3 and 5 Hz prolongs the duration of the SP and probably does so by altering the activity of the cortical inhibitory interneurons. 10,11 Here we now show that rTMS prolongs the cortical SP to a similar extent, also in patients with PD. The normal pattern of cortical SPs during rTMS in PD suggests that the cortical inhibitory interneurons mediating the SP as tested by rTMS function normally.…”
Section: Discussionmentioning
confidence: 81%
“…9 Besides altering the MEPs, trains of rTMS prolong the duration of the cortical SP evoked by magnetic stimuli. 10,11 Repetitive stimu-lation of the motor cortex therefore influences the activity of excitatory as well as inhibitory neural elements of cortical motor areas. We investigated the effects of rTMS on MEPs and cortical SPs in patients with PD.…”
mentioning
confidence: 99%
“…The primary purposes of included studies with healthy adult participants were to investigate the mechanisms underlying the effect of rTMS stimuli on transmission in corticospinal pathways 27,28,41,46 ; the effects of a specific dose of rTMS on transmission in corticospinal pathways 15,16,[32][33][34]36,42,45,47 ; the effects of different doses of rTMS on transmission in corticospinal pathways 21,30,38,39,40,43,44,50 ; the effects of 2 waveforms of rTMS 22,26,51 ; whether rTMSinduced changes in transmission in corticospinal pathways last beyond application of stimuli 31 ; the effects on movement control of using rTMS 35,42,48,52,53 ; the differences in response to rTMS between healthy adults and people with actual or potential movement disorder. [17][18][19][20] The primary purpose of the included study with participants after stroke was to investigate the effects of rTMS on recovery of movement after stroke.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to single-pulse or paired-pulse TMS, rTMS involves the application of trains of pulses at a constant rate to a cortical target. Depending on the stimulation protocol, rTMS can change regional excitability and neuronal activity from minutes to hours beyond the time of stimulation [4,10,11]. Because of a transsynaptic spread of excitation through cortico -cortical or cortico -subcortical connections, rTMS can produce conditioning effects in distant cortical [11,12] or subcortical areas such as the basal ganglia [13 -15].…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%